Fabrication and characterization of lead nickel niobate-lead zirconate titanate ceramics by using two-stage sintering technique - Kannika Niamsee (2018)
In this work, the effects of a two-stage sintering technique on phase formation, microstructure and dielectric properties of perovskite relaxor ferroelectric lead nickel niobate-lead zirconate titanate 0.2PNN-0.8PZT ceramics were investigated by using composition of X-ray diffraction (XRD), scanning electron microscopy (SEM) and dielectric measurements techniques. It was found that the density and grain size values were observed to increase with decreasing the first sintering temperature (T1) in two-stage sintering method. Under suitable sintering scheme (850/1150°C for 2 h), highly dense and pure-phase perovskite 0.2PNN-0.8PZT ceramics with maximum dielectric constant of about 22016 at 1 kHz were obtained. © 2013 Copyright Taylor and Francis Group, LLC.